Effect of Pressure Level and Slurry Particle Size on Solids and Protein Extractability During Cold Extraction - Yuwono, Sudarminto Setyo (Fakultas Teknologi Pertanian Universitas Brawijaya, 2001)
Aim of this study was to obtain information on the effects of extraction pressure and slurry particle size on the level of solids and protein extractability in soymilk. A completely randomized factorial design was employed in this series of the experiments. The experiments were carried out in duplicate. Two factors were varied : pressure level (2.5; 5; 10; 15; and 20 psi) and particle size of the slurry.(coarse, medium, fine, and very fine slurry). Results showed that both the level of pressure and the slurry particle size played a key role in solid and protein extraction. Besides that, this study also showed an increase the pressure while reducing the slurry particle size resulted in raising the yield and total solid, but not the protein content. The solid and protein extractability increased by applying a higher pressure on the finer slurry particle size. The highest extractability of solid and protein was 67.61 and 83.46%, respectively, achieved by the very fine slurry pressed at 20 psi. Whereas the coarse slurry produced the lowest result namely 57.69% for solid extractability and 72.27% for protein extractability. Â Keywords: cold extraction, extractability, soymilk